Evaluating Firm Value of Public Pharmaceutical Companies in Vietnam: A Capital Structure Assessment Approach - Adam, Bakar; Dinh Ngoc, Duong (2016)
Vietnam is a large and fast growing pharmaceutical market, with popupulation expected to reach 96 million by 2019. After a period of sustained and high economic growth during the years 2005-2007, since 2008, many Vietnamese pharmaceutical companies have planned to restructure themselves to survive and grow in the context of intensive economic integration. Capital restructuring is among many choices in the restructuring process of Vietnamese companies. This paper reviews literature on impact of capital structure on firm value and some empirical evidences in cases of public pharmaceutical companies in Vietnam.